Social Innovation - OCDE - OCDE (2021)
Social innovation refers to the design and implementation of new solutions that imply conceptual, process, product, or organisational change, which ultimately aim to improve the welfare and wellbeing of individuals and communities.
Keywords: International

TDR | Social innovation news - World Health Organization (WHO, 2021)
Keywords: International

Exemple - Rapport d'impact 2020-2021 - MILA (Mila, 2021)
Keywords: Intelligence artificielle; International; Libre accès; Mesure d'impact; Québec

Exemple - Rapport d'impact 2020-2021 - MILA (Mila, 2021)
Keywords: Intelligence artificielle; International; Libre accès; Mesure d'impact; Québec

Social Innovation - OCDE - OCDE
Social innovation refers to the design and implementation of new solutions that imply conceptual, process, product, or organisational change, which ultimately aim to improve the welfare and wellbeing of individuals and communities.
Keywords: International

TDR | Social innovation news - World Health Organization (WHO)
Keywords: International